APRESIASI PENDENGAR TERHADAP ACARA FUNKYNDO REQUEST DI RADIO NINETYNINERS BANDUNG - fitriah, maria (Jurnal Sosial Humaniora, 2011)
The main goal of this research is in order to know more about the appreciation of the listener to the program of Funkyndo Request in radio Ninetyniners. The research method that used is a quantitative description. The data gathering were done by using an observation, polling, interview, bibliography review. Sample determining was gained by sampling purposive because the taken sample based on criteria of twice song request and send message while the observer search and had already played role actively for about two years (2004 until 2006). Therefore the taken amounts of respondent are 84 person. The result depicts, that the cognitive as pact of respondent have already known about Funkyndo Request in radio Ninetyniners in a generally. The emotional aspect show, that generally respondent are satisfied of Funkyndo Request program. In this case, respondent level satisfaction is not maximal yet. That is mean, there is respondent necessary is not fulfill yet according to their request. Evaluative aspect show, that generally respondent have given a good mark toward the Funkyndo Request. In this case respondent evaluate that there is weakness in the program. In program duration respondent consider needed to add broadcast time more than two hours. Its means allowed more chance the listener for participating. Beside that respondent evaluate is not suitable in placed program time. It is caused by the time decided is 09.00-11.00 WIB coincident convenience. Therefore, regarding listenerÃ¢â¬â¢s appreciation suggested to make a change and to add time program.